N.M. DRUZHININ'S WORKS ABOUT THE DECEMBRISTS IN THE 1940s AND 1950s. - Zhiboyedov V. V. (Вестник Брянского государственного университета)
The development of historical science at its present stage is inextricably linked with the use of the achievements of previous generations of historians. The life and work of outstanding scientists will always attract the attention of those who want to understand the history of science and appreciate the contribution that they have made with their research work to the further development of historical science. The problem of studying the scientific community represented by its prominent representatives is relevant for modern science. An important and unresolved task so far is to solve the question of what is scientifically valuable in their heritage, and what is a tribute to time and has already lost its scientific significance. This task must be solved by considering separately the legacy of a scientist, tracing the evolution of his views throughout his creative life. The article highlights the little-studied facts of N.M. Druzhinin's scientific biography. The scientific heritage of academician N.M. Druzhinin mostly includes works in the field of socio-economic.